Retinal Parameters as Compared with Head Circumference, Height, Weight, and Body Mass Index in Children in Kenya and Bhutan - Grundy, Sara J. (Am J Trop Med Hyg, 2018)
The retina shares embryological derivation with the brain and may provide a new measurement of overall growth status, especially useful in resource-limited settings. Optical coherence tomography (OCT) provides detailed quantification of retinal structures. We enrolled community-dwelling children ages 3–11 years old in Siaya, Kenya and Thimphu, Bhutan in 2016. We measured head circumference (age < 5 years only), height, and weight, and standardized these by age and gender. Research staff performed OCT (iScan; Optovue, Inc., Fremont, CA), measuring the peripapillary retinal nerve fiber layer (RNFL) and macular ganglion cell complex (GCC) thicknesses. A neuro-ophthalmologist performed quality control for centration, motion artifact, and algorithm-derived quality scores. Generalized estimating equations were used to determine the relationship between anthropometric and retinal measurements. Two hundred and fifty-eight children (139 females, average age 6.4 years) successfully completed at least one retinal scan, totaling 1,048 scans. Nine hundred and twenty-two scans (88.0%) were deemed usable. Fifty-three of the 258 children (20.5%) were able to complete all six scans. Kenyan children had a thinner average GCC (P < 0.001) than Bhutanese children after adjustment for age and gender, but not RNFL (P = 0.70). In models adjusting for age, gender, and study location, none of standardized height, weight, and body mass index (BMI) were statistically significantly associated with RNFL or GCC. We determined that OCT is feasible in some children in resource-limited settings, particularly those > 4 years old, using the iScan device. We found no evidence for GCC or RNFL as a proxy for height-, weight-, or BMI-for-age. The variation in mean GCC thickness in Asian versus African children warrants further investigation.